(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Literature published case studies are analyzed rationally to conclude the performance parameters of bio-enzymes for soil stabilization. The various aspects of enzyme stabilization such as stabilization mechanism, soil types suitable for enzyme stabilization, enzyme application rates and stabilization durability are evaluated. The improvements in index and engineering properties of enzyme-stabilized soil are used as a measure of the degree of stabilization achieved